Hantaanvirus among urban rats from a slum area in Bangkok. - S. Tantivanich (2018)
A total of 106 rodents sera from slum Wat Phai Ton and slum Klong Toey were examined by immunofluorescent antibody assay during May to August 1990. The positive sera were further tested by plaque reduction neutralization test with the prototype hantaanvirus and the rat-associated hantaan like virus. Isolation attempts were also performed from their tissues. Antibody-positive rats were found in both slum areas, 32.7% in slum Wat Phai Ton and 5.6% in slum Klong Toey. Rattus norvegicus was the major species found positive. Positive plaque reduction neutralization results indicated that the infecting virus was antigenically similar to the strain of rat-associated hantaanvirus. The presence of low titer antibodies (IFA titer 32 to 128) may be an obstacle to isolation of associated virus using tissue culture.